SUBJECTS OF LEADERSHIP DEVELOPMENT IN PUBLIC MANAGEMENT ACTIVITIES - Storozhev R.І. (Pressing Problems of Public Administration, 2017)
The article defines the subjects of leadership in public administration activity on the basis ofunderstanding the speci city of leadership at the present stage, in the context of which the essenceof development of leadership in public management activity from the point of view of developmentof the personality of the civil servant and development of public management activity is considered.The components of the development process of leadership in public administration activities, inparticular, educational, organizational and normative-legal, have been identi ed.